Karakterisasi profil serangan pada jaringan dengan melakukan pemodelan terhadap lalu lintas data - Andinata, Phompi; Jusak, Jusak; Kusumawati, Weny Indah (Journal of Control and Network Systems, 2014)
: Network security became one of principal subtance in the world of information technology that alway experiencing developments. The rate of internet crime or cyber crime tended to increase as offered by publicist Kominfo Gatot S Dewa Broto throughout the year of 2012 in indonesia recorded an average of 1.25 million times per day. Genearlly hackers using a bias attack pattern know as DdoS (Distributed Denial of Service). The occurence of a DdoS attack is generally be preceded by pre-attack using media traffic data network. This step is to find security gaps bu using several techniques like port scanning ACK Scan, FIN Scan, SYN Scan or Scan tool by using a Port Scanner.To understand the statistical characteristics and pattern of some ACK Scan attacks, FIN Scan, SYN Scan and Port Scanner, in this project we do analysing and modeling of multiple attack in LAN and WAN networksResult of the analysis showed that the normal data traffic and data traffic that contains ACK Scan, FIN Scan, SYN Scan and Port Scanner in two netwok model (A) and (B) is lognormal with a comparison of Mean Square Error and the smallest value test of Anderson Darling compared to Gamma distribution and Weibull distribution